The role of alpha1-fetoprotein transcription factor/LRH-1 in bile acid biosynthesis: a known nuclear receptor actovator that can act as a suppressor of bile acid biosynthesis - Del Castillo-Olivares, Antonio; Campos-Sandoval, José Ángel; Pandak, William M.; Gil, Gregorio (American Society for Biochemistry and Molecular Biology, 2004)
Two key regulatory enzymes in the bile acid biosynthesis pathway are cholesterol 7alpha-hydroxylase/CYP7A1 (7alpha-hydroxylase) and sterol 12alpha-hydroxylase/CYP8B1 (12alpha-hydroxylase). It has been shown previously that hepatocyte nuclear factor-4alpha (HNF-4) and the alpha(1)-fetoprotein transcription factor (FTF) are activators of 7alpha-and 12alpha-hydroxylase transcription and that the small heterodimer partner (SHP) suppresses bile acid biosynthesis by heterodimerizing with FTF. However, the role of FTF in bile acid biosynthesis has been studied only in tissue culture systems. In heterozygous FTF knockout mice, 7alpha- and 12alpha-hydroxylase genes were expressed at 5-7-fold higher levels than in wild-type mice, an apparent direct contradiction to previous in vitro observations. This higher expression of the 7alpha- and 12alpha-hydroxylase genes resulted in a 33% higher bile acid pool in their gallbladders, bile more enriched in cholic acid, and a 13% decrease in plasma cholesterol levels. Adenovirus-mediated FTF overexpression in wild-type mice resulted in 10-fold lower expression of the 7alpha- and 12alpha-hydroxylase genes and up to 8-fold higher SHP expression, highlighting the dual role that FTF plays in different promoters. Shorter overexpression times still resulted in lower 7alpha- and 12alpha-hydroxylase expression, but unchanged SHP expression, suggesting that two different mechanisms are involved in the FTF-mediated suppression of 7alpha- and 12alpha-hydroxylase expression. This FTF-mediated suppression of the expression of two bile acid biosynthesis genes resulted in a 3-fold lower rate of bile acid synthesis in a rat bile fistula animal model. Based on these observations and on protein binding studies performed in vitro and by chromatin immunoprecipitation, we hypothesize that FTF has two synergetic effects that contribute to its role in bile acid biosynthesis.
Keywords: Ácidos biliares - Síntesis; Bile acids biosynthesis; Cholesterol 7alpha hydroxylase; Sterol 12-alpha hydroxylase; Hepatocyte nuclear factor 4-alpha; Small heterodimer partner; Alpha-1- fetoprotein; Promoter